Factors Related to Patient Satisfaction Level of Thyroid Tumor on Post- Operative Thyroidectomy Scar Based on Patient Scar Assessment Scale (PSAS) in General Hospital Dr. M. Djamil Padang - Heryadi, Defri; Daan Khambri; Rony Rustam (Biomedical Journal of Indonesia, 2021)
A B S T R A C TIntroduction : Dr. M. Djamil Padang General Hospital (RSUP) still appliesconventional methods as thyroidectomy treatment. Satisfaction and comfort to thescar is one of the issues because conventional thyroidectomy surgery scars arelocated in the neck area that will affect the confidence of patients, especially women.Method: This research was a quantitative research using cross sectional studydesign. The research was conducted at The Oncology Surgery Polyclinic of RSUPDr.M. Djamil Padang with a sample of 50 respondents. Result: More than half ofthyroid tumor patients found were women (56%), most patients had totalthyroidectomy surgery (70%) with malignan tumor type (72%), and the most tumorsize in the T4 group (52%). The average age of patients during surgery was 54.26years. The average patient satisfaction score for post-thyroidectomy scars was 14.72with a total score of 16, the lowest score was 6 and the highest score was 22.Significant relationships were found in variable tumor size (p= 0.000), type of surgery(p= 0.005), tumor type (p=0.004) and gender (p = 0.028), while there was nostatistically significant relationship between age and patient satisfaction with post-thyroidectomy scars (p=0,176). Conclusion: There were significant relationshipsbetween gender, type of surgery, type of tumor, tumor size to patient satisfactionwith post-thyroidectomy scars, while age has no signifacnt relationship to patientsatisfaction with post-thyroidectomy scars. A small number of PSAS score showedthat the average patient was satisfied with post-thyroidectomy scar.